2020
DOI: 10.1177/2151459320958202
|View full text |Cite
|
Sign up to set email alerts
|

Time-Driven Activity-Based Costing: A Better Way to Understand the Cost of Caring for Hip Fractures

Abstract: Geriatric hip fractures are a common and costly injury. They are expected to surge in incidence and economic burden as the population ages. With an increasing financial strain on the healthcare system, payors and providers are looking toward alternative, value-based models to contain costs. Value in healthcare is the ratio of outcomes achieved over costs incurred, and can be improved by reducing cost while maintaining or improving outcomes, or by improving outcomes while maintaining or reducing costs. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
(58 reference statements)
1
10
0
3
Order By: Relevance
“…In a study using radiology department subjects, Laurila et al (2020) also found that compared to traditional costing methods, activity-based costing was more precise in allocating overhead costs. Similar studies in the health unit also found the same thing, as conducted by Blaschke et al (2020), Suthummanon et al (2005, Claesson and Edgren (2001).…”
Section: Activity-based Costing In Service Companysupporting
confidence: 74%
See 1 more Smart Citation
“…In a study using radiology department subjects, Laurila et al (2020) also found that compared to traditional costing methods, activity-based costing was more precise in allocating overhead costs. Similar studies in the health unit also found the same thing, as conducted by Blaschke et al (2020), Suthummanon et al (2005, Claesson and Edgren (2001).…”
Section: Activity-based Costing In Service Companysupporting
confidence: 74%
“…(Nota et al, 2020 ;Raab et al, 2010;Bagherpour et al,2013). In service companies themselves, often the research subjects used are health services such as hospitals (Laurila et al,2020;Blaschke et al,2020, andShah, 2018), restaurant (Raab et al, 2010), library (Siguenza-Guzman et al,2014). There are still very few studies that use research subjects in the form of travel service companies.…”
Section: Introductionmentioning
confidence: 99%
“…2 Aside from procedural-level insights, which are well discussed in the review, TDABC is versatile enough to provide clinical insights, involving the evaluation of pathways, teams, and patients of different medical complexities across different subspecialties and conditions. 8 Furthermore, it can provide transparency around cost implications of process variations, including the addition of digital health tools and use of external services. 2 The review by Koolmees et al, along with several others, highlights variation in costs and thus the potential to inform clinicians and administrators ways to more effectively optimize resource allocation and waste reduction.…”
Section: Unlocking Value Through Agile Innovationmentioning
confidence: 99%
“…Similarly, most of the reviews carried out in the field have this departmental focus [ 36 ]. They are centred on a specific health area, such as surgery [ 39 ], oncology [ 1 ], obstetrics [ 40 ], or orthopaedics [ 41 , 42 ]. These reviews mainly focus on how the different methods (including ABC or TDABC) have measured a specific aspect within the study area [ 1 ], the variations in the use of the cost method itself, with the conclusion that it lacks standardization [ 42 ], or the comparison of profitability between different techniques [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%